Pengaruh Jangka Pendek dan Jangka Panjang Saham Global terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2015:M01 - 2020:M12 - Heru Wahyudi; Figa Ramani (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze the external and internal factors that affect the movement of the Composite Stock Price Index (IHSG) in Indonesia in the short and long term. External influences of global stock indices are DJIA, NIKKEI225 and SSEC, as well as the exchange rate (USD/IDR). The most influential internal influence is inflation. Research methodology: This study uses the ECM (Error Correction Model) method. ECM aims to determine the long-term and short-term effects of variables that affect the JCI in Indonesia. In addition, this study uses monthly time series data from January 2015 to December 2020. Results: The results of this study show that the DJIA index and Inflation have a positive and significant influence in the long and short term on the movement of IHSG in Indonesia. The SSEC and Exchange Rate Index (USD/IDR) have a negative and significant relationship in the long and short term to the movement of IHSG in Indonesia, while the NIKKEI225 index has no long-term or short-term influence on the movement of IHSG in Indonesia. Limitations: The limitation of this research is that there are many variables outside the model that are not included in the study Contribution: For investors who will start investing in the Indonesia Stock Exchange, before investing, they should pay attention to the movement of global stock indexes (DJIA and SSEC).